The Effects of Different Types of Feedback in the EFL Writing Class: A Study of Efficiency, Affective and Cognitive Aspects, and Thai Cultural Dimensions (European Journal of Teaching and Education, 2020)
The purposes of this research were to 1) compare the effects of self-correction, paper-pencil peer feedback, and online peer feedback on the students’ writing achievement; 2) compare the effects of the students’ levels of general English proficiency (high, moderate and low) on writing achievement; 3) investigate the interaction effect between the types of feedback and levels of general English proficiency on the students’ writing achievement; and 4) survey the students’ attitudes toward the use of feedback activity they experienced in terms of its efficiency, affective and cognitive aspects, and Thai cultural dimensions. The study was conducted with 72 engineering students having different levels of general English proficiency. They were randomly selected and assigned into three groups. Two-way Analysis of Variance (ANOVA), descriptive statistics, and content analysis were used to analyze the data. The questionnaire and interview were used to gain more in-depth data. The results revealed that the different types of feedback and levels of English proficiency had a significantly different effect on the students’ writing achievement, and the interaction effect was also found.